2005
DOI: 10.1002/pola.20871
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizer‐free dispersion copolymerization of maleic anhydride and vinyl acetate. I. Effects of principal factors on microspheres

Abstract: A novel dispersion copolymerization of maleic anhydride (MAn) and vinyl acetate (VAc) without adding stabilizer is developed, which gives uniform copolymer microspheres with tunable sizes. Some principal factors affecting the microspheres, such as reaction time, monomer concentration and feed ratio, reaction media, and cosolvent, were investigated. It was found that the stabilizer‐free dispersion copolymerization of MAn and VAc is a rapid process, and the particle size grows in accordance with the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Therefore, it is of practical value to develop a new, easy-to-control and environmentalfriendly productive technology. Recently, we reported a novel and facile method to prepare micro/nano-particles of alternating copolymers of MAH and vinyl acetate (16). These particles can be easily prepared in n-butyl acetate/n-heptane without use of any stabilizer or surfactant.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is of practical value to develop a new, easy-to-control and environmentalfriendly productive technology. Recently, we reported a novel and facile method to prepare micro/nano-particles of alternating copolymers of MAH and vinyl acetate (16). These particles can be easily prepared in n-butyl acetate/n-heptane without use of any stabilizer or surfactant.…”
Section: Introductionmentioning
confidence: 98%
“…[9,12,15] This may be attributed to the facile alternating copolymerization of MAn and VAc by a charge transfer complex (CTC) mechanism, as has been discussed in detail in our previous articles. [19,20] However, we found that the ultimate conversion of monomer was hard to be completed (around 80-90%). This can be interpreted from the phenomenon of phase separation in the dispersion polymerization process, which may lead to the ratio imbalance of MAn and VAc (i.e., beyond 1:1).…”
Section: Typical Kinetic Charactermentioning
confidence: 93%
“…[19,20] In comparison, the solution copolymerization of MAn and VAc in methyl propyl ketone was also conducted (with the standard recipe in Table 1, except that the solvent was replaced).…”
Section: Polymerization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The steric stabilizer brings out environmental pollution, cost increase of the product, change in the ultimate properties of polymer particles, and migration of stabilizer molecules. 10 Therefore, Xing et al 10,11 recently reported a dispersion copolymerization for the preparation of surface-clean polymer particles without any stabilizer or other additives. They performed the novel stabilizer-free dispersion polymerization with maleic anhydride and vinyl acetate in alkyl esters as the reaction medium.…”
Section: Introductionmentioning
confidence: 99%